Anmeldelser: Public Theologian avant la lettre? N.F.S. Grundtvig as Historian and Politician - Schmiedel, Ulrich (Grundtvig-Studier, 2019)
The Common Good: N.F.S. Grundtvig as Politician and Contemporary Historian, translated by Edward Broadbridge, edited by Edward Broadbridge and Ove Korsgaard, Aarhus: Aarhus University Press, 2019.